PENGARUH LINGKUNGAN KERJA, BEBAN KERJA, WORK LIFE BALANCE TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA KARYAWAN GENERASI Y DI BANK DANAMON - Suryadi Budi Setyo (2021)
This study aims to analyze the effect of the work environment, workload, work life balance on employee turnover intention. Quantitative methods are used in the study by taking the population, namely Generation Y through job satisfaction at Bank Danamon. Determination of the sample is done by simple random sampling technique. Data were collected through questionnaires through Google Forms, and statistical analysis was carried out using partial least squares with the SmartPLS version 3. The results of the analysis showed that: 1) Work environment and work life balance can increase job satisfaction significantly, but workload significantly reduces employee job satisfaction at Bank Danamon, 2) Work environment and work life balance can significantly reduce turnover intention, but workload significantly increases turnover intention in Generation Y employees at Bank Danamon, 3) Job satisfaction can mediate the influence of work environment, workl